STUDENTS ATTITUDE TO INTERDISCIPLINARY RESEARCH - Ahrens, Andreas; Zaščerinska, Jeļena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Interdisciplinary research helps to turn bi-modal nature of phenomenon into success as interdisciplinary research ensures the synergy between two contrasting modes or forms. However, students’ attitude to interdisciplinary research has not been analysed. The purpose of the contribution is to analyse students’ attitude to interdisciplinary research underpinning elaboration of a hypothesis on ensuring students’ positive attitude to interdisciplinary research within university studies. The meaning of the key concepts of “interdisciplinary research” and “students’ attitude” is studied. Moreover, the logical chain of analysis is shown: interdisciplinary research → students’ attitude → empirical study within a multicultural environment. Directions of further research are proposed. The novel contribution of the paper is the notion and phases of interdisciplinary research worked out by the paper’s authors.